Lights, camera, middle school! - Holm, Jennifer L.; Holm, Matthew (Holm, Jennifer L. Babymouse. Tales from the locker, 2022)
Middle-schooler Babymouse is tired of materialistic mean-girls who think all girls should be like them, so Babymouse decides to join the film club in order to stand out. But making a cinematic masterpiece is harder than Babymouse thought, and her dream may turn into a nightmare.